Sodium alginate encapsulated Moroccan clay as eco-friendly and efficient adsorbent for copper ions from aqueous medium. (2022) - Barrak, Ilias; Ayouch, Ikrame; Kassab, Zineb; El Achaby, Mounir; Barhoun, Abdeslam; Draoui, Khalid
Abstract: Water pollution with copper (Cu) has a significant impact on the environment and human health. Within this context, the present study aims to synthesize a composite bead based on Moroccan natural clay from Chaouia (CH) and sodium alginate (Na-AL) as adsorbents to remove copper ions from aqueous solution. The adsorbents were characterized using X-Ray Diffraction (XRD), Scanning Electron Microscopy coupled with Energy Dispersive X-ray (SEM-EDX) and Thermogravimetric Analysis (TGA). The effect of adsorbent dose, kinetic time, initial concentration of copper ions and temperature were investigated. Nonlinear regression was applied to fit the isothermal and kinetic models. The results showed that the clay is composed of kaolinite and quartz and the SEM confirmed the successful incorporation of sodium alginate into the clay. The adsorption process follows the Langmuir isotherm with a maximum adsorption capacity of 48.24 and 92.44 mg.g −1 for the clay (CH) and the beads composite designated as (CH@AL), respectively. Pseudo-second-order model best described the kinetic data. Moreover, the thermodynamics of the adsorption was spontaneous and endothermic. All of these results proved that the used adsorbents are eco-friendly and efficient for the adsorption of Cu(II) ions.